Tissue Engineering of Skin for Wound Coverage - Biedermann, Thomas; Boettcher-Haberzeth, Sophie; Reichmann, Ernst (European Journal of Pediatric Surgery, 2013)
Over the past few decades, important milestones have been reached in the field of skin tissue engineering, bringing the ultimate goal of fabricating an autologous dermoepidermal skin substitute with all its cellular components and skin appendages closer to reality. Yet, scientific progress alone is not enough, clinical demands must be addressed and commercial interests need to be fulfilled. This review gives an overview of commercially available skin substitutes for skin replacement therapies and an insight into the recent development of an autologous full-thickness skin substitute that can readily be transplanted in large quantities onto the patient.
Keywords: skin tissue engineering; skin substitute; dermal substitute; burn wound; chronic wound